Harness the internal stress in ceramics - Lianmeng Zhang (Journal of Materiomics, 2025)
Internal stress engineering has demonstrated remarkable potential in enhancing the mechanical and functional properties of ceramics. However, conventional regulation strategies relying on mismatch of thermal expansion coefficient encounter great challenges in terms of precise stress modulation and material selection. Recently, a novel internal stress regulation approach exploiting the mismatch of elastic modulus has been proposed to effectively break these limitations. Through precisely controlled external pressure during cold sintering process, the incorporated secondary phase with ultra-high modulus enables the creation of tunable internal stress reaching gigapascal in the matrix. This stress engineering strategy gives rise to significantly enhanced mechanical properties and unique functional characteristics of the ceramic matrix, which might greatly influence the future design of high-performance ceramic composites.